PENERAPAN METODE SIX SIGMA PADA PERBAIKAN MUTU PRODUKSI PERMEN - Wijaya, Leonardo Agusta; Saryatmo, Mohammad Agung; Kosasih, Wilson (Jurnal Mitra Teknik Industri, 2023)
This research focuses on KOHE candy products produced by PT. KS. PT. KS is a manufacturing company that produces candy. Based on the observations and research that has been done, there are defects or product defects during the process of making KOHE candy. This study aims to identify, analyze and provide suggestions for improvement for PT. KS in order to reduce the number of defects or product defects produced using the six sigma method. Based on the calculation of process capability and sigma value, product quality improvement is 15,136 DPMO with a sigma value of 3.67. Based on the FMEA, it can be seen that the causes of defects or product defects are candy squeezed between packages, placement of candy that does not fit, packaging that is not closed evenly and description of candy packaging that does not match. Based on the RPN calculation with the aim of determining the highest priority is a pinched packaging defect with an RPN value of 210 and a severity value of 7. The proposed improvements are improvements to work SOP, check sheets and one point lessons. It is hoped that this research can provide benefits in the form of reducing the number of defects during the production process at PT. KS.